Trust & Transparency: Promoting Efficient Corporate Disclosure Through Fiduciary-Based Discourse - Michael R. Siebecker (Washington University Law Review, 2009)
Could embracing the philosophy of “encapsulated trust” as the basis for a fiduciary duty of disclosure improve the integrity and effectiveness of corporate communications? The question arises because a tragedy of transparency threatens the viability of the burgeoning corporate social responsibility (CSR) movement, where consumers and investors employ various social, environmental, or ethical screening criteria before purchasing a company's stock or products. In an efficient market, fully informed consumers and investors could reward companies that engage in CSR by purchasing their products or stock and, conversely, punish companies that fail to engage in desired practices by refusing to purchase their products or stock. Unfortunately, corporations are increasingly engaging in a sort of “strategic ambiguity” in their public communications—an ambiguity made possible by a variety of static yet inconsistent standards regarding the collection, auditing, and dissemination of information regarding CSR practices. Consumers and investors simply cannot trust the existing disclosure regime to provide reliable information necessary to monitor CSR compliance. That lack of trust will cause the market for CSR to collapse, as consumers and investors stop offering rewards for responsible business behavior. The Article suggests solving that disclosure tragedy by using the philosophy of “encapsulated trust” to reshape the existing fiduciary duties governing officers and directors. In simple terms, encapsulated trust constitutes a rational expectation that others will take our interests into account when determining what course of action to pursue. Applied in the context of corporate disclosures on CSR, encapsulated trust would require officers and directors to demonstrate they took into account shareholder preferences regarding the timing, content, and form of corporate disclosures. In essence, the duty is a process-based standard that relies on continual discourse to improve the integrity of disclosure practices. In contrast to static statutory disclosure rules, an emphasis on improved discourse between the corporations and shareholders would promote greater efficiency in corporate communication by attending more accurately to evolving consumer and investor disclosure preferences. Moreover, the focus on greater discourse within the corporate setting would also lead to enhanced ethical practices by corporate actors and their counsel.
Keywords: Social responsibility of business; Corporate fiduciaries; Disclosure of information – Law & amp; legislation